Auto- and heterosuggestion in boat rowing - Omelyanenko, V. I. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Purpose. Creation of a complex integrated person-centered psychological model of sportsmen preparation for competitions in rowing and canoeing on base of heterosuggestion which includes psychological methods and their modifications as well as Rajah yoga system mindset trainings.